Pembinaan Koperasi Jamur Merekah Menuju Koperasi Modern - Deddy Supriyadi; M. Akmal R; Yuli Y; Salsadilla R; Hafidhah A.; Ferlin B. (LPPM Universitas Koperasi Indonesia, 2023)
The Development of Jamur Merekah Cooperative is carried out with the aim of upgrading the Jamur Merekah cooperative into a Modern Cooperative. The method used in this coaching is to go directly to the field/cooperative to collect the necessary data and information through observation, interviews with administrators, supervisors, employees and members, then identify potential and problems as well as the need for coaching then develop a coaching program. This activity was carried out for 1 month which was integrated with Student Field Practice activities. The substance of the material presented is the digitalization of cooperatives, preparation of financial reports and business development. For the effectiveness of this coaching activity, in practice coaching is carried out with observation and active participation of field practice students in cooperative processes in the field with the direction of the supervisor. Furthermore, discussions and discussions were carried out with the management and supervising lecturers so that these coaching materials were then applied in cooperatives. Coaching activities can run well as planned. The Jamur Merekah Cooperative has the potential to develop and become a modern cooperative. It's just that for that Cooperatives must make improvements and carry out business development continuously and consistently.